Photocatalytic NOx abatement by calcium aluminate cements modified with TiO2: Improved NO2 conversion. (April 2015) - Pérez-Nicolás, M.; Balbuena, J.; Cruz-Yusta, M.; Sánchez, L.; Navarro-Blasco, I.; Fernández, J.M.; Alvarez, J.I.
Abstract: Photocatalytic activity of TiO2 was studied in two types of calcium aluminate cement (CAC) under two different curing regimes. The effect of the TiO2 addition on the setting time, consistency and mechanical properties of the CACs was evaluated. The abatement of gaseous pollutants (NOx ) under UV irradiation was also assessed. These cementitious matrices were found to successfully retain NO2 : more abundant presence of aluminates in white cement (w-CAC, iron-lean) helped to better adsorb NO2, thus improving the conversion performance of the catalyst resulting in a larger NOx removal under UV irradiation. As evidenced by XRD, SEM, EDAX and zeta potential analyses, the presence of ferrite in dark cement (d-CAC, iron-reach) induced a certain chemical interaction with TiO2 . The experimental findings suggest the formation of new iron titanate phases, namely pseudobrookite. The reduced band-gap energy of these compounds compared with that of TiO2 accounts for the photocatalytic activity of these samples.